A prioritization approach based on VFT and AHP for group decision making: a case study in the military operations - Ygor Logullo; Vinícius Bigogno-Costa; Amanda Cecília Simões da Silva; Mischel Carmen Belderrain (Production)
Abstract Paper Aims This paper aims to develop an approach to support group decision making combining methods and tools to a holistic MCDA process. Originality Authors have been using Value-Focused Thinking (VFT) for structuring problems with different MCDA methods, but there is a lack of a process that defines a clear transition from VFT to those methods. Here we propose a process to fill this gap. Research method Rich Picture and VFT structure the problem and elicit objectives that become criteria within a decision hierarchy. Analytic Hierarchy Process (AHP) with ratings supports preference elicitation and sensitivity analysis in the judgment weights of decision-makers. Main findings VFT is effective for eliciting the decision structure to AHP; using weight distribution of stakeholders may affect the results, and the multimethodology approach developed here can deal with group decision making. Implications for theory and practice The approach developed is effective in complex environments (complex problems and multiple stakeholders) because it focuses on values and defines a process to bring those values into a multicriteria method. Furthermore, sensitivity analysis with the judgment weights of the different stakeholders may be useful in negotiation.